Hydrological characterization of the Araguaia River through reference flows - Rodolfo Rosario Klautau de Araujo Gomes; Lindemberg Lima Fernandes (Applied Water Science, 2017)
Abstract This study examined the hydrological behavior of the Araguaia River through reference flow, analyzing the capacity of granting the river segments in three different fluviometric stations. The study exposed the comparison of monthly and annual reference flow, considering a hydrological series of 33 years. Consequently, it was proposed seasonal flow comparing to the methodology of annual reference flow for water grants in national rivers. The adoption of the annual reference flow restricts the grants of water use in most of the time, because the proposal of monthly and seasonal Q 95% in the rainy period for grants processes showed much higher values. The proposal of monthly and seasonal reference flows to grant the multiple right of use of water may be the most adequate for power generation, because it presents the inherent characteristics of the flows of each month and per period, respectively. However, the use of seasonality for grants must be analyzed along with the environmental aspect of the river basin concerning to the damage of aquatic life of the Araguaia River.